Case Study: Recombinant Bromelain Selection - Azura, Amid; Nurul Azira, Ismail; Zatul Iffah, Mohd Arshad (Springer International Publishing, 2015)
This chapter presents an investigation that we performed prior to the decision to proceed cloning and producing recombinant bromelain. The criteria that we examined were the following: (1) easy access to a DNA source; (2) broad application; (3) an enzyme size amenable to the cloning strategy; (4) available data in free online databases; (5) broad industrial application.